1983
DOI: 10.1002/star.19830350405
|View full text |Cite
|
Sign up to set email alerts
|

Physico‐Chemical Properties of Defatted Heat‐Moisture Treated Starches

Abstract: Physico-chemical properties of wheat-and potato starch, defatted before or after heat-moisture treatment, were compared with those of untreated starches. Effects on waterbindingcapacity, swelling power, solubility, enzyme susceptibility, gelatinization temperature range, viscograph consistency and on functional properties such as cake baking performance and thickening power are reported. X-ray diffraction patterns of samples defatted before heating appeared slightly sharper than those of non-defatted, then hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 7 publications
2
11
0
Order By: Relevance
“…However, the impact is dependent on the type of starch to which the treatments are applied. Heat‐moisture treatment at 110 °C with 15, 20 and 25% moisture decreases crystallinity and increases α‐amylase susceptibility of rice starch, similar to what has been found with wheat and potato . However, heating corn starch to 110 °C with 20, 25, 30 and 35% moisture increased crystallinity and decreased in vitro digestibility .…”
Section: Effect Of Heat‐moisture Treatment On Composition and Rice Stsupporting
confidence: 71%
See 1 more Smart Citation
“…However, the impact is dependent on the type of starch to which the treatments are applied. Heat‐moisture treatment at 110 °C with 15, 20 and 25% moisture decreases crystallinity and increases α‐amylase susceptibility of rice starch, similar to what has been found with wheat and potato . However, heating corn starch to 110 °C with 20, 25, 30 and 35% moisture increased crystallinity and decreased in vitro digestibility .…”
Section: Effect Of Heat‐moisture Treatment On Composition and Rice Stsupporting
confidence: 71%
“…Heat‐moisture treatment such as parboiling, cooking, annealing and extrusion (Table ) reduces starch crystallinity . During heat‐moisture processing, starch undergoes gelatinisation, a complex process of irreversible disruption of the double helical crystalline structure of starch (Figure ).…”
Section: Effect Of Heat‐moisture Treatment On Composition and Rice Stmentioning
confidence: 99%
“…The increase in digestibility by amylase after heat-moisture treatment suggests a change in orientation of the starch polymers in the granules by the treatment followed by a certain degree of degradation which rendered the starch more accessible to amylase, as previously report- ed [9]. Digestibility increases in the heated starches may also be attributed to gelatinization of starch, characterized by irreversible swelling of the granules, increase in viscosity as the order and crystallinity of the starch molecules are broken down by heat allowing more water penetration and hydration of the granules [16].…”
Section: In Vitro Digestibility Of Rice Starches Heattreated In Microsupporting
confidence: 48%
“…Heat-moisture treatment of wheat starch caused a considerable reduction in relative crystallinity and resulted in increased enzyme susceptibility [9]. Secondly, it has been observed that the dehydration which accompanies heatmoisture treatment of starch changes the crystallographic pattern of the starch granules leading to the conversion of a fraction of amorphous amylose to the crystalline form [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation